Post surgery pain coping culture on infirmary personnel - Ortega-López, Rosa Margarita (Universidad Autónoma de Tamaulipas, 2010)
The purpose of this research was to identify pain management, attitudes and meanings that builds the nurse with postoperative patients. The methodology was done through a qualitative study, where the total population was twelve nurses of the surgical area of a public hospital in secondary care. Results were obtained as nurses consider different factors related to the manner in which the hospitalized person expresses the pain, “cultural level, source of patient, age and sex, ethnicity, language and/or dialect, educational level, previous experiences with pain, religion and consciousness of the patient. “And the significance of postoperative pain define it as “unpleasant sensation, severe pain, the surgical demonstration, overwhelming sense of pain, emotional. And he concluded that the nurse cares for and helps the patient to mitigate, remove, manage, control and prevent pain, plus it has the power to bind the person hospitalized with the resources of the hospital, own family and the nurse to alleviate and manage pain.